Crystal structure and Hirshfeld surface analysis of (E)-6-(4-hydroxy-3-methoxystyryl)-4,5-dihydropyridazin-3(2H)-one - Said Daoui; Cemile Baydere; Fouad El Kalai; Rafik Saddik; Necmi Dege; Khalid Karrouchi; Noureddine Benchat (Acta Crystallographica Section E: Crystallographic Communications, 2019)
In the title compound, C13H14N2O3, the dihydropyridazine ring (r.m.s. deviation = 0.166 Å) has a screw-boat conformation. The dihedral angle between its mean plane and the benzene ring is 0.77 (12)°. In the crystal, intermolecular O—H...O hydrogen bonds generate C(5) chains and N—H...O hydrogen bonds produce R22(8) motifs. These types of interactions lead to the formation of layers parallel to (12\overline{1}). The three-dimensional network is achieved by C—H...O interactions, including R24(8) motifs. Intermolecular interactions were additionally investigated using Hirshfeld surface analysis and two-dimensional fingerprint plots. The most significant contributions to the crystal packing are by H...H (43.3%), H...C/C...H (19.3%), H...O/H...O (22.6%), C...N/N...C (3.0%) and H...N/N...H (5.8%) contacts. C—H...π interactions and aromatic π–π stacking interactions are not observed.